CLÉS D’IDENTIFICATION DES IXODINA(ACARINA) D’ALGERIE (Sciences & Technologie. C, Biotechnologies, 2006)
During ten years (1985-1995), an investigation carriedout in the North-East of Algeria on ticks infesting domestic livestock and wildanimals (cattle, sheep, dog, turtleand wild boar) enabled us to rise the first identification key of 15 species of Ixodina dealing with larvae, nymphs, females and males of 6 genera: Ixodes, Boophilus, Dermacentor, Hyalomma, HaemaphysalisetRhipicephalus.